TEKS GEGURITAN RARE KUMARA ANALISIS BENTUK, FUNGSI, DAN MAKNA - Aryanti, Depi (Humanis; Volume 12. No.1. Juli 2015)
The research about Geguritan Rare Kumara Text: Form Analysis, Function and Meaning is aimed to describe the form, function and meaning of the Geguritan Rare Kumara (GRK) itself. Theory used in this research is structural theory, theory of functions and semiotic theory. Teeuw’s structural theory is used to analyze the GRK structure. Function theory is by Ratna, to find out the function of a literature in the community. Umberto Eco’s semiotic theory is used to determine the meaning inside of the GRK. The research is conducted by using method and techniques which is data provision technique and method, data analysis technique and method, and presentation result method and technique. The provision stage is using literature method by heuristic readings, continued with hermeneutics readings. Analysis stage is using descriptive method by outlines the data source more detail. The presentation result analysis is using informal method, deductive and inductive method. GRK is form of storytelling using pupuh formulation and stylistic comparison, conflict and convergence. There are also traditional stylisti (basita paribasa) called cacimpedan. GRK also has narrative structure. GRK serves as source of story the puppet Sapuh Leger performance, reflection of education and intellectual point to wariga wisdom. The GRK contained some meanings as follows: meruat papa meaning, enlightenment which is based on self-control and knowledge about ista dewata and rwa bhinneda meaning.
Keywords: discourse, ruatan, geguritan, form, function and meaning